2018
DOI: 10.15575/jtk.v3i2.3713
|View full text |Cite
|
Sign up to set email alerts
|

Pembelajaran Sistem Koloid Melalui Media Animasi Untuk Meningkatkan Aktivitas Dan Hasil Belajar Siswa

Abstract: Telah dilakukan penelitian yang bertujuan untuk menganalisis peningkatan hasil belajar siswa pada konsep sistem koloid dalam pembelajaran melalui media animasi. Penelitian ini merupakan jenis penelitian tindakan kelas yang ditempuh dalam dua siklus. Setiap siklus terdiri dari empat tahap yaitu tahap perencanaan, pelaksanaan, pengamatan, dan refleksi.  Subjek penelitian adalah 33 orang siswa SMKN 2 Cimahi kelas XI Teknik Kimia Industri. Teknik pengumpulan data menggunakan tes tertulis, angket dan observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
8
0
2
Order By: Relevance
“…An example of a page containing an animation of washing clothes with soap can be seen in Figure 8. Shortcomings in previous studies where the learning media animation about the colloidal system (Eli & Sari, 2018). Flash based can only run on Windows operating systems and can only be used via a computer.…”
Section: Development Of Web-based Chemical Learningmentioning
confidence: 99%
See 3 more Smart Citations
“…An example of a page containing an animation of washing clothes with soap can be seen in Figure 8. Shortcomings in previous studies where the learning media animation about the colloidal system (Eli & Sari, 2018). Flash based can only run on Windows operating systems and can only be used via a computer.…”
Section: Development Of Web-based Chemical Learningmentioning
confidence: 99%
“…The implementation of the learning process that is less than the maximum can be seen from their learning outcomes which showed that 5% of students in class XI of Industrial Chemical Engineering had grades below the KKM (Minimum completeness criteria). Based on these data it can be said that learning outcomes of chemistry students are low (Eli & Sari, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biokimia pada Materi Metabolisme Karbohidrat untuk Mahasiswa Program Studi Kimia lain yang juga mendukung pentingnya penggunaan pembelajaran dengan bantuan e-module sebagai sarana komunikasi yang lebih efektif sehingga dapat meningkatkan hasil belajar peserta didik yang ditunjukkan melalui naiknya nilai rata-rata kelas pada siklus I dan siklus II (Eli & Sari, 2018). Diperkuat juga oleh penelitian Sari & Samawi (2014) mengenai pengaruh media animasi terhadap hasil belajar IPA, peserta didik slow learner menunjukkan hasil adanya peningkatan pemahaman peserta didik terhadap mata pelajaran IPA dengan kategori baik.…”
Section: Pengembangan E-moduleunclassified